Inventory management of selected carinderias in Iloilo City - Mamon, Karel Mae R.; Peniero, Claire L.; Platon, Ruth C.; Solis, Anjeanette G.
Carinderias as part of a micro-enterprise encounter problems regarding proper inventory management. With the increasing problems of carinderias in Iloilo City, the study aims to describe the inventory management practices and tools utilized by them. Also, the study intends to identify and assess the inventory management issues and problems they encounter and recommend measures to address and improve those. This study used a qualitative methodology due to its appropriateness for the nature of the study. A purposive sampling technique is utilized in selecting the respondent enterprises for the study and the primary data were collected through an interview-scheduled questionnaire. Respondent carinderias were selected according to the following criteria : (1) the business should be at least 10 years in operation ; and (2) is located in Iloilo Terminal Market and Iloilo Central Market. The data gathered from the respondents were analyzed using frequency distribution, mean and thematic analysis. Based on the results and analysis of the study, it was found out that most of the respondents do not track their inventories and only few of the respondents utilize a manual method for tracking. The majority of the respondents store different types of inventories but with no large storage except for refrigerators. In terms of the tools, results indicate that the majority of carinderias were unfamiliar with the names and concepts presented. In terms of identifying names of the tools they are familiar with, mostly identified safety stock but when presented with activities from varied tools, it was found out that they always use Just-in-time in their operations. On problems and issues identified, more than half of the respondents have problems regarding their storage of inventories. Inventory management of the respondents based on the results are affected also by external factor such as safety of the premises, increased competition, and changing demands. As such, measures such as having an inventory sheet, maintaining an organized inventory storage, extensive use of inventory management system, conducting training and seminars, and investing in technology are formulated to improve the inventory management of carinderias.